Real-Time Cure Monitoring of Unsaturated Polyester Resin from Ultra-Violet Curing - Hussein, Mahmoud A; Tay, G. S.; Rozman, H. D. (Journal of Research Updates in Polymer Science, 2012)
Real time Fourier transform infrared (RTFT-IR) spectroscopy reveals the influence of the nature of the photoinitiator on the kinetics for the polymerization reaction. Real time cure monitoring was used to determine the polymerization rate of ultra-violet cured unsaturated polyester resins (UPR1:2-1:5) based on palm oil and containing styrene as a cross-linking agent in the presence of IRGACURE 184 photoinitiator. Firstly, variable types of UPR1:2-1:5 were prepared using various ratios of monoglyceride (MG) monomer to maleic anhydride which used as a source of double bond using polycondensation technique. RTFT-IR spectroscopy was used to characterize the ultra-violet curing kinetics for all the systems. This technique offered a powerful approach for monitoring changes in the chemical properties of the system during the ultra-violet curing. Pseudo first order kinetics for all UPR1:2-1:5 curable systems were determined and the rate constant values and regression coefficients were calculated. Furthermore, the thermal behaviour and morphological features for the photo-fabricated UPR1:2-1:5 systems were examined. The thermal analyses for the cured films were evaluated by TGA, DTG and DSC in nitrogen atmosphere at a heating rate of 10°C/min. All the formulations showed similar degradation pattern at 40 % and 50 % weight losses (Td = 40% and Td =50% respectively) except polymer UPR1:5 which had somewhat lower degree in the same range. In addition, the morphological properties for photo-fabricated UPR1:2,1:3,1:5 were investigated by using scanning electron microscopy.